ANALISIS TINGKAT KEAMANAN DATA PADA SALAH SATU KANTOR PERPAJAKAN DI BEKASI YANG RENTAN TERHADAP SERANGAN CYBER DALAM SISTEM KEUANGAN - Ahmad Septian; Teuku Alfiansyah, Aji Dewa Abdulla, Hedi Sutiawan, Dwi Ali Ega Fauzi, Dimas Hadi Saputra, Tubagus He (ADISAM PUBLISHER, 2024)
Cybercrime refers to crimes committed using computer technology or the Internet. This includes malicious attacks, theft of personal data, online fraud, and other illegal activities in the digital world. Tax accounting is a financial recording activity in a business entity or institution to find out the amount of tax that must be paid, technically apart from functioning to find out the amount of tax that must be paid. taxpayers must pay, this accounting branch also has other functions such as annual tax documentation, financial reports, analytical materials to determine the amount of tax that must be paid. Threats to the security of financial data are growing rapidly. Cybercriminals are increasingly sophisticated and able to exploit security vulnerabilities in digital systems, including malicious attacks, hacking and sophisticated network attacks. In recent years, there have been quite large cases of data security breaches, such as what happened in 2021. hacking of financial system data at one of the tax offices. Therefore, data security is very important to pay attention to and improve the quality of security by the office. The research method used in this research is a qualitative method and involves a literature study that focuses on financial management systems and security management systems in offices. reviewing various related documents, books and journals to find out how pe.